Case report: a patient with spontaneous spinal epidural hematoma recovered after conservative treatment - Cheng, Jingge; Li, Bo; Liu, Shuaiye; Liu, Yiming; Zhao, Yipeng (Frontiers in Medicine, 2025)
Spontaneous spinal epidural hematoma is a rare condition, akin to a stroke, which can manifest as hemiplegia. It cannot be diagnosed by head CT scan and is prone to misdiagnosis as a cerebral stroke, potentially leading to the activation of thrombolysis and exacerbation of the condition. This paper reports a case of a patient with this disease, a 68 years-old male who presented with sudden neck pain weakness, and numbness in the left limbs for 2 h. The symptoms were similar to those of a stroke. A head CT scan showed no significant abnormalities, but the clinical presentation of neck pain alerted the physician, who did not hastily administer thrombolysis. Instead, they quickly performed further examinations, including neck vessel ultrasound and neck CT/MRI, to rule out a cerebral stroke. The patient was ultimately diagnosed with spontaneous spinal epidural hematoma in the neck. The patient was transferred to the ICU for conservative treatment, and a follow-up neck MRI the next day revealed a significant reduction in the hematoma, with a corresponding improvement in clinical symptoms. This case report supports the diagnostic value of CT scans for spinal epidural hematoma and shares a conservative treatment plan for patients with high spinal cord lesions.